A Conceptual Model to Establish an Islamic Finance Unit at a Malaysian Public University - Abdullah, Adam (Canadian Center of Science and Education, 2014)
This paper seeks to propose a new conceptual model to establish an Islamic Finance Unit (IFU) at a public university in Malaysia in order to extend benevolent interest-free financing as an act of charity. The problem with conventional student financing is the extent of non-performance due to the interest component. This paper identifies the need, justification and implementation of establishing the IFU, and measures success through equity and justice, not from charging interest, but returns generated from fees derived from increased student enrollment. The model could equally apply to any private or public university, and involves a blue ocean strategy in support of the development of new academic programmes by providing financing to improve the welfare of students and the local community.